MODERATING EFFECT OF FIRM SIZE ON THE EFFECT OF PROFITABILITY ON CAPITAL STRUCTURE IN THE PECKING ORDER THEORY PERSPECTIVE - Rahmat Setiawan (Universitas Islam Lamongan, 2022)
This paper aims to examine (1) the effect of profitability on capital structure and (2) the moderating effect of firm size on the effect of profitability on capital structure in the perspective of Pecking Order Theory . Based on the Pecking Order Theory , when a company needs funding to finance its investment, the company will prioritize its internal funding sources (retained earnings) first, and when the internal funding sources are insufficient, then the company will use external funding sources. When a company uses external funding sources, the company will prioritize sources of funding from debt, only then will the company use equity shares. In the perspective of Pecking Order Theory , profitability has a negative effect on capital structure (level of leverage or level of use of debt), which means that the higher the profitability of the company, the lower the level of leverage of the company. The theoretical explanation is that the higher the company's profitability, the higher the company's retained earnings potential. Companies that have high retained earnings potential will tend to finance their investments using retained earnings, so these companies will have a low level of leverage or level of debt use. In the perspective of the Pecking Order Theory , firm size will weaken the negative effect of profitability on the level of leverage . Companies with large sizes have low information asymmetry so that it is easier to get external funding from debt. Therefore, the negative effect of profitability on the level of leverage will be weaker in large companies compared to small companies.